The genetics of the Drosophila achaete-scute gene complex: a historical appraisal. - Campos-Ortega, J.A. (International Journal of Developmental Biology, 1998)
The Drosophila achaete-scute complex consists of four genes encoding transcription factors of the bHLH family. Due to their intricate organization, these genes have occupied geneticists and developmental biologists for many years. Here, genetic studies on the complex are discussed from a historical point of view.